PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMAN 2 TEBAS - Dewi, Desi Isromi; Hairida, Hairida; Melati, Husna Amalya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrack This study aims to determine whether there is a difference between the studentâ€™slearning motivation of grade XI of SMA NEGERI 2 TEBAS in the materials ofelectrolyte and nonelectrolyte solution using Think Pair Share (TPS) learning modelsand using conventional learning model, and determining the influence of its models onlearning outcomes. The research form used is quasi experiment with as research designâ€œnonequivalent control group pretest-posttestâ€. Sampling using a saturated samplingtechnique. Data collection tecniques are measurement tecniques. Data collection toolused is a quetionnaire of student learning motivations and essay test. Motivationhypothesis test using independent sample t test ( independent samples T-test) at the reallevel = 5% yields sig value. (2-tailed) of 0.000 so that Ha received (Ho rejected), thisshows the difference motivation of students learning experimental class and controlclass. The test of learning result hypothesis using U-mann whitney test yields Asympvalue. Sig. (2-tailed) by 0.005 so that Ho is rejected, it shows the difference of thestudentâ€™s learning result of the experimental class and the control class. Learning byusing cooperative type Think Pair Share (TPS) gives an increase in learning outcome of91.9%. Keywords : Think Pair Share, Motivation, Learning Outcomes.